2016
DOI: 10.1186/s12959-016-0083-3
|View full text |Cite
|
Sign up to set email alerts
|

Giant right ventricular outflow tract thrombus in hereditary spherocytosis: a case report

Abstract: BackgroundIn hereditary spherocytosis with severe anemia, splenectomy is a recommended treatment. However, the spleen carries an important role both in immune function and coagulation. The increased risk of bacterial infections associated with splenectomy is well known. Recently, hypercoagulation disorders have also been linked to splenectomy through loss of regulation of platelet activity, loss of filtering function and post-splenectomy thrombocytosis.Case presentationA 28 year-old smoking women who had previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The previous studies have shown that common complications of total splenectomy include postoperative infection, OPSI, surgical bleeding, injury of adjacent organs, and VTE (2,12,13). The most severe complications of PSE are abdominal infection and spleen abscess formation, which is deadly for patients in severe cases (14).…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies have shown that common complications of total splenectomy include postoperative infection, OPSI, surgical bleeding, injury of adjacent organs, and VTE (2,12,13). The most severe complications of PSE are abdominal infection and spleen abscess formation, which is deadly for patients in severe cases (14).…”
Section: Discussionmentioning
confidence: 99%
“…Most patients' symptoms resolve within 1 week after surgery. Previous studies have shown that common complications of total splenectomy include postoperative infection, OPSI, surgical bleeding, injury of adjacent organs and venous thromboembolism (VTE) 2,12,13 . The most serious complications of PSE are abdominal infection and spleen abscess formation, which is deadly for patients in severe cases 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Few cases of thromboembolism have been reported with a link to hereditary spherocytosis (HS), particularly in patients with a prior history of splenectomy. 5 9 We present a case of a patient who was transferred from an outside hospital showing non-ST elevation myocardial infarction (NSTEMI) and who subsequently was diagnosed with CE.…”
Section: Introductionmentioning
confidence: 99%